Dynamics of apex and leaf development in barley as affected by PPD-H1 alleles in two contrasting PHYC backgrounds under short or long photoperiod - Parrado, Jorge D.; Savin, Roxana; Slafer, Gustavo A. (Frontiers in Plant Science, 2024)
Barley development from seedling to flowering involves both external and internal changes, the latter requiring microscopic observation. Internal changes allow characterising pre-flowering development into three phases: vegetative, early reproductive, and late reproductive. Genetic and environmental factors influence the duration of these phases, impacting in grain yield. Photoperiod-sensitivity genes PPD-H1 play a major role in flowering time, affecting adaptation, however the effect might also be direct (beyond affecting phenology). In this paper, we aimed to assess how PPD-H1 alleles affect barley development, including the progression of growth phases, leaf emergence, tillering dynamics, and spikelet development. Two experiments (field-and controlled-conditions) were conducted with a factorial combination of (i) four near isogenic lines (NILs) for PPD-H1 alleles (ppd-H1 or Ppd-H1) under two contrasting PHYC genetic backgrounds (PhyC-l and PhyC-e), and (ii) two photoperiod conditions (short and long days). As expected, longer photoperiods led to a shorter growth cycle. All sub-phases of time to flowering, final leaf number and phyllochron were affected by photoperiod. The effects of PPD-H1 on flowering time depended on the PHYC genetic backgrounds and photoperiod conditions. PPD-H1 effects on flowering time were associated to leaf number and phyllochron, the interplay between leaf number and phyllochron affected mainly the late reproductive phase. We also found that although PPD-H1 did not affect phyllochron of the first 6 leaves, but that of leaves appearing later, when grown under short photoperiod, was consistently increased in lines carrying ppd-H1 allele. Tillering dynamics exhibited variability, but PPD-H1 did not affect final spike number under 24 h photoperiod.